Analisis Penerapan Akuntansi Isak 35 Pada Organisasi Keagamaan (Studi Kasus 5 Masjid Di Kabupaten Labuhanbatu Selatan) - Rinda Arista; Nurlaila Nurlaila; Atika Atika (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research aims to analyze the application of ISAK 35 accounting standards in religious organizations by taking case studies of five mosques in South Labuhanbatu Regency. ISAK 35 is an accounting standard that regulates the recognition, measurement, and placement of transactions and events in hazardous organizations. In the context of religious organizations, namely mosques, the implementation of ISAK 35 has an important importance in ensuring transparency and accountability in financial management. This research uses a qualitative approach with a case study method. Primary data was collected through in-depth interviews with mosque administrators and related financial staff. Secondary data was obtained through literature and documentation studies related to the implementation of ISAK 35 in religious organizations. The research results show that five mosques located in South Labuhanbatu Regency still have not implemented the ISAK 35 standard in preparing their financial reports. This shows that there are deficiencies in the presentation and delivery of financial information in accordance with applicable accounting standards. This research provides an overview of the importance of implementing ISAK 35 standards in producing more transparent, accurate and trustworthy financial reports for mosques in the region. These factors include limited knowledge and understanding of ISAK 35 by mosque administrators, a lack of human resources skilled in accounting, and a lack of support from external parties such as local governments or financial supervisory bodies.